Wild problems in the theory of representations of *-algebras generated by generatrices and relations - Piryatinskaya, A. Yu.; Samoilenko, Yu. S. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
Two definitions of wild *-algebras are considered from the point of view of the theory of representations. We present methods for proving the fact that a *-algebra is wild. It is also shown that if a algebra isp-wild, then it isf-wild. The converse statement is not true.